2019
DOI: 10.1002/anie.201902656
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous trans‐Selective Transfer Hydrogenation of Apolar Boron–Boron Double Bonds

Abstract: The transfer hydrogenation of N-heterocyclic carbene (NHC)-supported diborenes with dimethylamine borane proceeds with high selectivity for the trans-1,2-dihydrodiboranes.D FT calculations,s upported by kinetic studies and deuteration experiments,s uggest as tepwise proton-first-hydride-second reaction mechanism via an intermediate m-hydrodiboronium dimethylaminoboratei on pair.Since the 1925 landmark discovery by Meerwein and Verley of the aluminum alkoxide-promoted hydrogenation of ketones using alcohols as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
7
0
2
Order By: Relevance
“…74 Furthermore, Braunschweig and co-workers recently showed that Me 2 NHBH 3 can be used to isolate hydrogenated diborenes; thus, analogous reactivity is anticipated. 75 However, in our hands, stoichiometric reactions of 3 and Me 2 NHBH 3 resulted in a mixture of species, whilst reaction with a higher number of equivalents of Me 2 NHBH 3 resulted in the dehydrocoupling products. We therefore conclude that the dialumene acts as a pre-catalyst in this reaction and the active catalyst is generated in situ.…”
Section: Co 2 Hydroborationmentioning
confidence: 52%
“…74 Furthermore, Braunschweig and co-workers recently showed that Me 2 NHBH 3 can be used to isolate hydrogenated diborenes; thus, analogous reactivity is anticipated. 75 However, in our hands, stoichiometric reactions of 3 and Me 2 NHBH 3 resulted in a mixture of species, whilst reaction with a higher number of equivalents of Me 2 NHBH 3 resulted in the dehydrocoupling products. We therefore conclude that the dialumene acts as a pre-catalyst in this reaction and the active catalyst is generated in situ.…”
Section: Co 2 Hydroborationmentioning
confidence: 52%
“…The reductive coupling of N‐heterocyclic carbene (NHC)‐stabilized (NHC)BX 2 R (R=Br, Ph) precursors, for example, provided access to neutral di‐ and tetrahydrodiboranes of the form [(NHC)R′HB‐BHR′(NHC)] (R′=H, Ph), whereas that of [ArBH 2 ] 2 diborane(6) precursors yielded [ArH 2 B‐BH 2 Ar] 2− dianions which were in turn converted via double hydride abstraction to neutral dihydrodiboranes(4) . Milder routes to diboranes with terminal B−H bonds include the dehydrocoupling of boranes, selective dimethylamino‐hydride exchange at B 2 N 2 C 2 heterocycles, the spontaneous transfer hydrogenation of diborenes with Me 2 NH⋅BH 3 , or the insertion of a borylene into a B−H bond at a boron cluster …”
Section: Methodsmentioning
confidence: 99%
“…While studying the stoichiometric transfer hydrogenation of the ferrocene-bridged diborene 1 [15] with Me 2 NH•BH 3 , we observed, beside the expected 1,2-dihydrodiborane (d 11B = À18.0 ppm), a second product (d 11B = 88.6, À29.6 ppm, 1:2 ratio), which we deemed to result from the reaction of 1 with the dehydrocoupling byproduct Me 2 N = BH 2 . [10] Similarly, the reaction of 1 with 1 equiv pyrrolidinoborane (PyrBH 2 ) in C 6 D 6 at 60 8C overnight resulted in quantitative formation of the triborane 2-Pyr (Scheme 2), which shows two broad 11 B NMR resonances at d 11B = 87.8 (sp 2 -B) and À28.8 (sp 3 -B) ppm in a 1:2 ratio and a 1 H{ 11 B} NMR BH resonance (2 H) at…”
mentioning
confidence: 99%
“…So ermöglichte beispielsweise die reduktive Kupplung von N‐heterocyclischen Carben (NHC)‐stabilisierten (NHC)BX 2 R (R=Br, Ph)‐Vorstufen den Zugang zu neutralen Di‐ und Tetrahydrodiboranen der Form [(NHC)R′HB‐BHR′(NHC)] (R′=H, Ph), während [ArBH 2 ] 2 Diboran(6)‐Spezies zu Dianionen [ArH 2 B‐BH 2 Ar] 2− reduziert wurden, welche wiederum durch doppelte Hydridabstraktion in neutrale Dihydrodiborane(4) überführt wurden . Mildere Reaktionsbedingungen für die Bildung von Diboranen mit terminalen B‐H‐Bindungen beinhalten die Dehydrokupplung von Boranen, den selektiven Dimethylamino‐Hydrid‐Austausch an B 2 N 2 C 2 Heterocyclen, die spontane Transferhydrierung von Diborenen mit Me 2 NH⋅BH 3 oder die Insertion eines Borylens in eine B‐H‐Bindung eines Borclusters …”
Section: Methodsunclassified